Pre-diagnosis fiber : carbohydrate intake ratio and mortality of ovarian cancer: results from a prospective cohort study. Issue 19 (12th September 2022) - Liu, Fang-Hua; Du, Zong-Da; Li, Xin-Yu; Wei, Yi-Fan; Wen, Zhao-Yan; Yan, Shi; Sun, Ming-Li; Qin, Xue; Gao, Song; Gong, Ting-Ting; Wu, Qi-Jun
Abstract : The association between the ratio of fiber to carbohydrate (F : C-R) and cancer mortality is not currently well-known. Abstract : Background : The association between the ratio of fiber to carbohydrate (F : C-R) and cancer mortality is not currently well-known. We prospectively evaluated for the first time the aforementioned topic among ovarian cancer (OC) patients. Methods : A total of 703 newly diagnosed OC patients aged 18–79 years were included. Pre-diagnosis diet intake details were collected with a validated food frequency questionnaire. Deaths were ascertained until March 31, 2021, based on medical records and the cancer registry. Cox proportional hazard models were used to evaluate hazard ratios (HRs) and 95% confidence intervals (CIs) between pre-diagnostic fiber, carbohydrate, and F : C-R intake and OC mortality. Restricted cubic splines were used to analyze the potential nonlinear relationship between F : C-R and OC mortality. Results : During the follow-up period (median: 37.2 months; interquartile: 24.7–50.2 months), we observed 130 (18.49%) OC patients died. The pre-diagnosis higher fiber intake (comparing the highest with the lowest tertile of intake: HR = 0.56, 95% CI = 0.35–0.92; HR per 1 SD increment: 0.78, 95% CI = 0.64–0.96; P trend < 0.05) and higher F : C-R intake (comparing the highest with the lowest tertile of intake: HR = 0.51, 95% CI = 0.31–0.85; HR per 1-SD increment: 0.73; 95% CI = 0.59–0.91; P trend < 0.05) were significantly associated with lower mortality for OC patients, but no evidence of the association between pre-diagnosis carbohydrate intake and OC mortality was observed. We found no evidence of a nonlinear relationship between F : C-R and OC mortality. Significant inverse associations were also observed for subgroup analyses stratified by age at diagnosis, menopausal status, residual lesions, histological type, FIGO stage, and body mass index, although not all associations showed statistical significance. Conclusion : Pre-diagnosis high fiber intake and high F : C-R diet intake were associated with a decreased risk of OC mortality.